Western blot technique standardization of the diagnosis of human fasciolosis using Fasciola hepatica excreted-secreted antigens. - Aorga, H.M.E. (2011)
Objectives: To evaluate the performance of the enzyme-linked immunoelectrotransfer blot assay (EITB, Western blot) using excretory/secretory antigens from adult forms of Fasciola hepatica (Fh E/S Ag) for the diagnosis of human fasciolosis. Materials and methods: Antigens were obtained after 18 hours of incubation in culture medium Minimum Essential Eagle, prepared at a protein concentration of 0.15 ug/uL and run against a pool of sera of patients with proven fasciolosis (confirmed by the finding of parasite eggs in the stool microscopy). Antigens of 10, 12, 17, 23, 27, 30, 36, 43, 66 and 136 kDa were detected and used to develop the Western blot technique. The sensitivity was evaluated using sera from 67 fasciolosis patients, and the specificity using sera from 57 patients with other parasitic diseases, and 10 from healthy individuals. Results: Out of the 67 sera, 64 reacted with the 23 kDa band and 61 with the one of 17 kDa. These two bands were not detected in sera from patients with other parasitic diseases or in those from healthy volunteers and thus could be considered specific and diagnostic. Conclusions: The sensitivity of the test, using the bands of 17 and 23 kDa, was 95.5% for positive reactions to at least one of these two bands, being its specificity 100% with a positive predictive value of 100% and negative predictive value of 95.71%.